Artificial intelligence basics a non-technical introduction - Taulli, Tom 1968- (Gildan Media, 2021)
Artificial intelligence touches nearly every part of your day. While you may initially assume that technology such as smart speakers and digital assistants are the extent of it, AI has in fact rapidly become a general-purpose technology, reverberating across industries including transportation, healthcare, financial services, and many more. In our modern era, an understanding of AI and its possibilities for your organization is essential for growth and success. Artificial Intelligence Basics has arrived to equip you with a fundamental, timely grasp of AI and its impact. Author Tom Taulli provides an engaging, non-technical introduction to important concepts such as machine learning, deep learning, natural language processing (NLP), robotics, and more. In addition to guiding you through real-world case studies and practical implementation steps, Taulli uses his expertise to expand on the bigger questions that surround AI. These include societal trends, ethics, and the future impact AI will have on world governments, company structures, and daily life. AI is the present and the future of your business as well as your home life. Strengthening your prowess on the subject will prove invaluable to your preparation for the future of tech, and Artificial Intelligence Basics is the indispensable guide that you've been seeking.
Online resource; title from title details screen (OverDrive, viewed July 27, 2021)
Keywords: Artificial intelligence; Machine learning; Business enterprises -- Technological innovations; Artificial Intelligence; Intelligence artificielle; Apprentissage automatique; Entreprises; Innovations; artificial intelligence; Business enterprises; Technological innovations; Downloadable audio books; Audiobooks; Livres audio